2015
DOI: 10.1002/2015jd023545
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the phase transition of Pacific Decadal Oscillation to the late 1990s' shift in East China summer rainfall

Abstract: Based on our previous study, the interdecadal changes in summer rainfall over East China in the late 1990s are further explored here. The increased local rising motion is implicated as the dominant factor of increased rainfall in the lower Huang‐Huai River valley (LHR). Both the observation and numerical experiments using Community Atmosphere Model, version 4 suggest that the negative Pacific Decadal Oscillation (PDO) mode can result in rising anomalies and thus more rainfall in the LHR. The East Asian westerl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 60 publications
5
76
0
Order By: Relevance
“…It is clear that the anomalies on the difference map of model experiments are opposite with those on the difference map of the two epochs in NCEP2 (figure not shown). Therefore, the PDO may not be the main direct reason for the decadal shift of the WPSH's influence on Asian summer climate (more designed details of model experiment can be seen in Zhu et al 2015). It is possible that the PDO may contribute to the changed SSTA forcing for the WPSH variability and shows its indirect influence on the decadal shift of the WPSH's influence on Asian summer climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the anomalies on the difference map of model experiments are opposite with those on the difference map of the two epochs in NCEP2 (figure not shown). Therefore, the PDO may not be the main direct reason for the decadal shift of the WPSH's influence on Asian summer climate (more designed details of model experiment can be seen in Zhu et al 2015). It is possible that the PDO may contribute to the changed SSTA forcing for the WPSH variability and shows its indirect influence on the decadal shift of the WPSH's influence on Asian summer climate.…”
Section: Discussionmentioning
confidence: 99%
“…Influences of the recent negative phase of PDO on the decadal change of Asian summer climate have been studied. For example, Zhu et al (2015) have examined contributions of the negative phase of PDO after the late 1990s to the summer rainfall anomalies over East Asia by using numerical model experiments. Does the changed PDO phase contribute to the decadal shift of the WPSH's influence on the Asian summer climate?…”
Section: Discussionmentioning
confidence: 99%
“…[] also showed the evidence that the southward displacement of ASWJ is influenced by anthropogenic forcing. Meanwhile, natural variability such as Pacific Decadal Oscillation (PDO) and Atlantic Multidecadal Oscillation (AMO) is also suggested to affect the meridional displacement of ASWJ [ Zhu et al ., ]. The interdecadal to multidecadal variability have great influence on the regional climate change, and the influences of AMO and PDO on central Asian climate are also noted in previous studies [ Meehl et al ., ; Dong and Dai , ; Wu et al , ].…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Understanding the characteristics and mechanisms responsible for this cold-to-warm SST regime shift is vital in view of its potential impacts on the climate variability over the Indo-Pacific basin. The present study is important while considering the decadal changes observed in the tropical cyclone activity over the SCS (He et al 2015), East Asian summer monsoon (Zhu et al 2011(Zhu et al , 2015Si and Ding 2013) and Indian summer monsoon (Yun et al 2010) in the late 1990s. The usage of multiple data products has limited our study from presenting a comprehensive discussion about the relative importance of air-sea heat fluxes and SCSTF/ PDO on the SST regime shift.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent regime shift in the global climate was observed in 1999 coinciding with the switching of PDO to a negative phase. Significant changes in the East Asian summer monsoon (EASM), EASM-ENSO relationship and SCS sea surface height have been observed since the late 1990s (Zhou et al 2007;Zhu et al 2011Zhu et al , 2015Si and Ding 2013;Song and Zhou 2015;Pei et al 2015). The EASM and ENSO have exhibited a strong correlation during .…”
mentioning
confidence: 93%